Nt-RhoGDI2 regulates Rac/Rop signaling and polar cell growth in tobacco pollen tubes - Klahre, Ulrich; Becker, Claude; Schmitt, Arno Christian; Kost, Benedikt (The plant journal, 2006)
Rac/Rop-type Rho-family small GTPases accumulate at the plasma membrane in the tip of pollen tubes and control the polar growth of these cells. Nt-RhoGDI2, a homolog of guanine nucleotide dissociation inhibitors (GDIs) regulating Rho signaling in animals and yeast, is co-expressed with the Rac/Rop GTPase Nt-Rac5 specifically in tobacco (Nicotiana tabacum) pollen tubes. The two proteins interact with each other in yeast two-hybrid assays, preferentially when Nt-Rac5 is prenylated. Transient over-expression of Nt-Rac5 and Nt-RhoGDI2 depolarized or inhibited tobacco pollen tube growth, respectively. Interestingly, pollen tubes over-expressing both proteins grew normally, demonstrating that the two proteins functionally interact in vivo. Nt-RhoGDI2 was localized to the pollen tube cytoplasm and effectively transferred co-over-expressed YFP-Nt-Rac5 fusion proteins from the plasma membrane to this compartment. A single amino acid exchange (R69A), which abolished binding to Nt-RhoGDI2, caused Nt-Rac5 to be mis-localized to the flanks of pollen tubes and strongly compromised its ability to depolarize pollen tube growth upon over-expression. Based on these observations, we propose that Nt-RhoGDI2-mediated recycling of Nt-Rac5 from the flanks of the tip to the apex has an essential function in the maintenance of polarized Rac/Rop signaling and cell expansion in pollen tubes. Similar mechanisms may generally play a role in the polarized accumulation of Rho GTPases in specific membrane domains, an important process whose regulation has not been well characterized in any cell type to date.